Changes to body mass index, work self-efficacy, health-related quality of life, and work participation in people with obesity after vocational rehabilitation: a prospective observational study - Anita Dyb Linge; Chris Jensen; Petter Laake; Stål Kapstø Bjørkly (BMC, 2021)
Abstract Background People on or at risk of sick leave from work due to obesity or obesity-related problems participated in a new vocational rehabilitation (VR). The study aimed to examine the outcome changes in the participants' health-related quality of life (HRQoL), body mass index (BMI), return to work self-efficacy (RTWSE), work ability scale (WAS) and degree of work participation (DWP) after their participation in the 12-month VR programme. The secondary aim was to examine associations between the outcome changes and HRQoL at 12-month follow-up, measured with the HRQoL 15D instrument (15D). Methods This prospective observational study included 95 participants. The one-year multidisciplinary VR programme with an integrated work and lifestyle intervention included 4 weeks of inpatient stay followed-up by 5 meetings. A paired sample t-test was used to examine changes in HRQoL, BMI, RTWSE, WAS, and DWP between baseline and the 12-month follow-up. Multiple linear regression analyses explored associations between changes in HRQoL and the outcome variables. Results The participants achieved statistically significant changes in HRQoL (2.57, 95% CI: 1.35 to 3.79), BMI (− 2.33, 95% CI: − 3.10 to − 1.56), RTWSE (15.89, 95% CI: 4.07 to 27.71), WAS (1.51, 95% CI: 0.83 to 2.20) and DWP (18.69, 95% CI: 8.35 to 29.02). At 12 months, a significant association was found between HRQoL and BMI (B = − 0.34, 95% CI: − 0.65 to − 0.04), RTWSE (B = 0.02, 95% CI: 0.004 to 0.04), WAS (B = 0.91, 95% CI: 0.55 to 1.28), DWP (B = − 0.02, 95% CI: − 0.04 to 0.001) and work absence (B = − 0.01, 95% CI: − 0.02 to − 0.002). The regression model explained 71.8% of the HRQoL variance. Conclusion The results indicated positive changes in HRQoL, BMI, RTWSE, WAS and DWP from baseline to the 12-month follow-up. Factors associated with HRQoL at the 12-month follow-up were decreased BMI, increased RTWSE, improved WAS and reduced work absence. Future studies examining VR programmes with lifestyle interventions for people with obesity are recommended. Trial registration Norwegian Regional Committee for Medical and Health Research Ethics (REC) 2017/573, Clinical Trials NCT03286374 , registered 18. September 2017. https://clinicaltrials.gov/ct2/results?cond=Obesity&term=Anita+Dyb+Linge&cntry=NO&state=&city=&dist=